Some Aspects of Legal Regulation of the Dismissal from Work: Features, Types and Social Guarantees - S. M. Bortnyk (Law and Safety)
Based on the analysis of the norms of general and special labor legislation of Ukraine, the author has researched the problem of legal regulation of one of the preventive measures of labor law – dismissal from work. The procedure of dismissal from work within the mechanism of legal regulation mainly performs a preventive function. The problem of dismissal from work in labor law has not been studied enough. A number of provisions regulating the relationship that has developed in case of dismissal are scattered across various regulatory acts. Some of those relationships are not regulated at all.